Thermodynamics, diffusion and the kirkendall effect in solids - Paul, Aloke (Springer International Publishing, 2014)
Covering both basic and advanced thermodynamic and phase  principles,  as well as providing stability diagrams relevant for diffusion studies, Thermodynamics, Diffusion and the Kirkendall Effect in Solids maximizes reader insights into Fick's laws of diffusion, atomic mechanisms, interdiffusion, intrinsic diffusion, tracer diffusion and the Kirkendall effect. Recent advances in the area of interdiffusion will be introduced, while the many practical examples and large number of illustrations given will serve to aid researches working in this area in learning the practical evaluation of various diffusion parameters from experimental results. With a unique approach to the two main focal points in solid state transformations, energetics (thermodynamics) and kinetics (interdiffusion) are extensively studied and their combined use in practise is discussed. Recent developments in the area of Kirkendall effect, grain boundary diffusion and multicomponent diffusion are also covered extensively. This book will appeal to students, academicians, engineers and researchers in academic institutions, industry research and development laboratories.